2019
DOI: 10.1186/s12885-019-5393-y
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma transformation in mature cystic teratoma of the ovary: a systematic review

Abstract: Background0.17–2% of mature cystic teratoma of the ovary (MCTO) undergo malignant transformation, of which 80% are squamous cell carcinoma (SCC) transformation in MCTO. We aim to investigate the clinical characteristics and treatment of SCC transformation in MCTOMethodsWe systematically searched PubMed database and individual patient data about SCC transformation in MCTO were extracted. The published cases were combined with 6 cases of SCC transformation in MCTO from Qilu Hospital, Shandong University.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
146
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(151 citation statements)
references
References 104 publications
3
146
2
Order By: Relevance
“…[4, 13] Several studies suggested that chemotherapy with BEP can be used in ovarian SCC. [14] Nevertheless our patient had a poor effect to the chemotherapy with BEP, which may lead to the recurrence within a short period of time.…”
Section: Discussionmentioning
confidence: 69%
“…[4, 13] Several studies suggested that chemotherapy with BEP can be used in ovarian SCC. [14] Nevertheless our patient had a poor effect to the chemotherapy with BEP, which may lead to the recurrence within a short period of time.…”
Section: Discussionmentioning
confidence: 69%
“…[4,13] Several studies suggested that chemotherapy with BEP can be used in ovarian SCC. [14] Nevertheless our patient had a poor effect to the chemotherapy with BEP, which may lead to the recurrence within a short period of time.…”
Section: Treatment Of Ovarian Sccmentioning
confidence: 69%
“…Surgery is the recommended course of treatment for primary colorectal SCC. In cases of ovarian teratomas with malignant transformation, hysterectomy can improve overall survival and was performed in our case [26]. A preoperative combined CRT can be performed in rectal SCC for improved local disease control.…”
Section: Discussionmentioning
confidence: 84%